Frequency of Hepatitis “B” Vaccination in Already Diagnosed “HCV” Positive Patients (Medical Forum Monthly, 2024)
Objective: To determine the frequency of Hepatitis “B” vaccination in already diagnosed “HCV” positive patientsStudy Design: Descriptive, cross-sectional.Place and Duration of Study: This study was conducted at the Department of Medicine, DHQ Teaching Hospital Bannu, Khyber Pakhtunkhwa for a period of 6 months from Feb 2015 to Aug 2015.Materials and Methods: Data was collected from 371 patients already diagnosed as HCV positive for more than 1 year, through a preset questionnaire, to note their vaccination status against HBV.Results: Out of 371 HCV positive patients, 201 patients were males (54.2%) and 170 (45.8%) were females. Only 89 (23.99%) patients were vaccinated (49 males and 40 females) while the rest were either non-vaccinated (260 patients i.e. 70.08%, 140 males and 120 females) or partially vaccinated (22 patients i.e. 5.93%, 12 males and 10 females). So overall 282 (76.01%) HCV positive patients were lacking proper vaccination against HBV, and merely 89 patients were properly vaccinated against HBV.Conclusion: The frequency of vaccination against HBV was very low in this high risk adult group patients (18-60 years) already infected with HCV. Only 89 (23.99%) patients were vaccinated, which is an alarming situation and need proper planning by health care providers.